Screening for Zn solubilisation potential of soil bacteria from Zn deficient soils of Kerala - Kumar, Aathira. S.; Meenakumari, K. S.; Anith, K. N. (Journal of Tropical Agriculture, 2017)
Zinc plays an important role among the micronutrients that influence plant growth and productivity. Various microorganisms like bacteria and fungi have been reported to solubilise insoluble sources of zinc present in soil. In the present study, microorganisms capable of solubilising insoluble forms of zinc like zinc oxide and zinc phosphate were isolated from zinc deficient soils of Kerala. Ten isolates of bacteria which were able to solubilise insoluble form of zinc (zinc oxide) were obtained. The size of the solubilisation zone ranged from 8.67 mm to 13.33 mm for zinc oxide and 1.00 mm to 5.33 mm for zinc phosphate incorporated selective medium. In broth culture, maximum zinc solubilisation in both sources were observed on 30th day in the range of 35.91 ppm to 104.08 ppm for zinc oxide supplemented medium and 1.38 ppm to 4.15 ppm for zinc phosphate supplemented medium. The isolate ZSB-4 showed highest solubilisation of zinc in plate assay and broth assay. Morphological and molecular characterization studies revealed the identity of the bacteria as Bacillus cereus. The isolate ZSB-4 significantly increased the available zinc content in soil from 0.55 ppm to 9.47 ppm under soil incubation studies.